2022
DOI: 10.3748/wjg.v28.i22.2429
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic aspects of hepatitis C virus

Abstract: Many metabolic factors are associated with chronic hepatitis C virus (HCV) infection and can influence the course of the illness and impact the progression of liver and non-liver-related diseases through complex interactions. Several of these factors impact the course of chronic HCV (CHC) and result in the conceptual translation of CHC from a localized to systemic disease. Besides the traditional liver manifestations associated with CHC infection, such as cirrhosis and hepatocellular carcinoma, various extrahe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…Combined with the current research, bone loss in patients with hepatitis may be caused by the metabolism of the body and a series of inflammatory reactions after infection with the hepatitis virus. Because abnormal metabolism can easily lead to malnutrition, systemic inflammatory response and malnutrition can cause skeletal muscle loss, both of which are risk factors for bone loss ( 30 32 ). The interaction of various factors increases the risk of bone loss in patients with hepatitis virus infection.…”
Section: Discussionmentioning
confidence: 99%
“…Combined with the current research, bone loss in patients with hepatitis may be caused by the metabolism of the body and a series of inflammatory reactions after infection with the hepatitis virus. Because abnormal metabolism can easily lead to malnutrition, systemic inflammatory response and malnutrition can cause skeletal muscle loss, both of which are risk factors for bone loss ( 30 32 ). The interaction of various factors increases the risk of bone loss in patients with hepatitis virus infection.…”
Section: Discussionmentioning
confidence: 99%
“…In the metabolic disorder scenario, several studies demonstrated that the replication cycle of HCV is strongly linked to the lipid metabolism pathway in hepatocytes (15)(16)(17)(18)(19) . The development of enveloped viral particles relies on hepatic very-low-density lipoprotein (VLDL) assembly, and this process originates numerous circulating lipoviral particles, which are generated by a fusion of virions and lipoproteins (15)(16)(17)(18)(19)(20) .…”
Section: Introductionmentioning
confidence: 99%
“…In the metabolic disorder scenario, several studies demonstrated that the replication cycle of HCV is strongly linked to the lipid metabolism pathway in hepatocytes (15)(16)(17)(18)(19) . The development of enveloped viral particles relies on hepatic very-low-density lipoprotein (VLDL) assembly, and this process originates numerous circulating lipoviral particles, which are generated by a fusion of virions and lipoproteins (15)(16)(17)(18)(19)(20) . Therefore, the lipid haemostasis is completely modified in patients with chronic hepatitis C (CHC) and this metabolic dysregulation might increase the risk of cardiovascular disease among HCV-infected persons (21)(22)(23)(24)(25)(26)(27)(28) .…”
Section: Introductionmentioning
confidence: 99%
“…HCV can lead to chronic hepatitis, cirrhosis, and hepatocellular carcinoma (HCC). Extrahepatic manifestations include polyarthritis, systemic vasculitis, lymphoproliferative diseases, renal disorders, type 2 diabetes, and pancreatic cancer [ 4 , 5 ]. There is no HCV vaccine currently available on the market, and access to diagnostics and treatment in many countries is low [ 3 ].…”
Section: Introductionmentioning
confidence: 99%